CYBER-SECURITY DAN TANTANGAN PENGEMBANGANNYA DI INDONESIA - Handrini Ardiyanti (Jurnal Politica, 2014)
Indonesia is reportedly facing a serious cyber-security threat due to the fact that the level of cyber crime in the country has reached critical condition. Unlike in coping with other crimes, to counter cyber-security, a comprehensive solutions should be found out. This paper discusses the ways of how cyber-security in the country has been handling, how its prospect, and new challenges coming from its development today.